Public funding of social protection: Impact on social indicators in Eurozone countries - Chugunov, Igor Ya.; Nasibova, O. (LLC “Consulting Publishing Company "Business Perspectives", 2021)
Social protection has long been a relevant subject of scientific debate. Its development is interrelated with the study of fiscal factors (collection of social contributions), establishment of major social protection vectors, and confirmation of hypotheses about the link between social protection policy and the resulting socio-economic indicators. The purpose of the paper is to study the impact of public funding of social protectionon social indicatorsusing the example of Eurozone countries. To this end, a number of economic and mathematical methods of analysis were applied to process panel data of seventeen countries for the last fifteen years, including the calculation of the relative rate of variation, regression dependence statistics, and cluster analysis. The study established the irrelevance between the scope of the fundingof spending on social protection and social contributions (coefficient of determination R2=0.255). As illustrated, social indicators are determined not only by the amount of funding of social spending, but also by the structure of the social protection system, in particular, the focus on assistance to families with children and disability compensation (coeffi cient of determination R2>0.3). The general level of public funding for social spending items results in the 69% income inequality index andis behind 58% of non-economic parameters affecting life quality. The information outlined in the papercan serve as a basis for the formation of social and budgetary policy, as well as the revision of the structure and scope of social protection funding toensure an efficient impact on the quality of life of the population.
Keywords: social contributions; social spending; the Gini coefficient; social progress index; social indicators; quality of life